COVID-19 preferred practice pattern for eye care professional - An initiative by Nepal Ophthalmic Society - Limbu, Ben; Khatri, Anadi; Joshi, Purushottam; Lamichhane, Gyanendra; Manandhar, Anu; Pradhan, Kishore; Pradhan, Eli; Badhu, Badri Prasad (Nepalese Journal of Ophthalmology, 2020)
Not available.